Monetary Policy Efficiency in Czech Economy Between 1998–2023 - Liu, Yu (2024)
The master thesis investigates the efficiency of monetary policy in the Czech Republic from the first month of 1998 to the last month of 2023, following the Czech National Bank's adoption of an inflation-targeting regime in 1998. Despite targeting an annual 2% consumer price index growth rate (CPI), deviations from this target during financial crises and the recent COVID-19 have raised concerns regarding the efficiency of monetary policy. The short-term normal interest rate is a central instrument used by the Czech National Bank to maintain price stability. Therefore, this thesis aims to explore the impact of monetary policy, particularly through the interest rate channel, on the Czech economy from 1998 to 2023. The hypothesis is that monetary policy in the flexible inflation channel has had a non-negligible effect from 1998 to 2023 during periods of adopting the inflation regime. In the theoretical part, I describe an in-depth overview of the historical evolution and mechanisms of monetary policy, discussing various channels such as interest rate and credit exchange rates, asset prices, and expectations, and how they affect monetary policy efficiency, alongside the price puzzle phenomenon. It also gives the perspective of the interactions between monetary, fiscal, and macroprudential policies. The empirical part reviews relevant empirical literature, and presents key Czech macroeconomic indicators from 1998 to 2023, excluding the period from 2013 to 2017. Analyzes the synchronization with the Euro Area. The Structural Vector Autoregression model is employed to interpret monetary policy efficiency through impulse response functions. The study concludes with a discussion of the limitations and policy implications of my empirical findings.